PEMBELAJARAN RISET OPERASI BERBASIS ICT PROGRAM KOMPUTER PADA MAHASISWA PROGRAM STUDI MATEMATIKA - Dwijanto, Dwijanto; Mashuri, Mashuri; Hidayah, Isti (Jurnal Penelitian Pendidikan, 2016)
Thisstudy was based on the results of learning innovation research conducted in Mathematics Department, Faculty of Mathematics and Science, Semarang State University. The expected goal is to develop or acquire a learning model mathematics course on ICT-based Operations Research. This study was done in order to utilize computer technology (laptop) that was shared by almost all students of the Department of Mathematics in order to reduce the difficulty of students to perform calculations that are many and complex.Research was conducted at the Laboratory of MathematicsUnneswhich also becomes the avenue of this subject. Implementation of learning by using the PBL approach (projectbased learning) based on ICT. The processed data was taken from the field (a real problem) which was further discussed and discussed in groups by utilizing the theory of operations research and facilities laptop and software that support it. The result of the discussion was presented in front of the class andeach step that has been done until the students reached their conclusion and interpretation. The results of the study concluded that (1) the form of the program to resolve the research operations problem was computer assisted program, and (2) the learning outcomes of operations research with project-based learning approach.